Measuring honesty and explaining adulteration in naturally occurring markets - Devesh Rustagi; Markus Kroell (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
There is astounding variation in product quality sold in markets even when quality is difficult to ascertain and rules are poorly enforced. We investigate whether sellers differ in innate honesty (incur private cost to provide good quality) and whether this explains the variation in quality. Our study takes place in milk markets in India, where milkmen collude on price, customer rarely switch, and it is difficult to establish reputation. We invite milkmen to take part in a novel behavioral experiment to measure dishonesty. We then measure quality objectively as the percentage of water added to a liter of milk sold to customers. Our results show that dishonest milkmen add significantly more water to milk. Evidence from milk- testing tournament confirms that milk quality is difficult to verify. These results suggest that some sellers are willing to forego monetary gains to provide good quality in return for utility from being honest, even in an environment that encourages cheating.
Keywords: C93; D91; O13; Q01; 330; Honesty; adulteration; milk markets; asymmetric information; measurement error; India